2014
DOI: 10.1080/09540121.2013.869537
|View full text |Cite
|
Sign up to set email alerts
|

Stigma in Ethiopia: association with depressive symptoms in people with HIV

Abstract: Rates of depression among people living with HIV can be as high as 50%. In many settings, HIV-related stigma has been associated with depressive symptoms which may lead to poor engagement in care and ultimately, poorer health outcomes. Stigma is a major issue in Ethiopia but data examining the relationship between stigma and depression in Ethiopia are lacking. We performed a mixed-methods cross-sectional study to examine the relationship between stigma of HIV/AIDS and depressive symptoms in Gondar, Ethiopia. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
40
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 20 publications
12
40
0
Order By: Relevance
“…A Ugandan study found 39% of their 447 HIV positive participants from ages 18–49 years screened positive for probable depression (Kaida et al, 2012). Higher levels of HIV-related stigma were significantly associated with elevated depressive symptoms (Endeshaw, Walson, Rawlins, Dessie, Alemu, Andrews, & Rao, 2014). Thus intervening at the PMTCT level itself might reduce psychiatric morbidity and improve adherence and engagement in the program (Abrams, Myer, Rosenfield, & El-Sadr, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…A Ugandan study found 39% of their 447 HIV positive participants from ages 18–49 years screened positive for probable depression (Kaida et al, 2012). Higher levels of HIV-related stigma were significantly associated with elevated depressive symptoms (Endeshaw, Walson, Rawlins, Dessie, Alemu, Andrews, & Rao, 2014). Thus intervening at the PMTCT level itself might reduce psychiatric morbidity and improve adherence and engagement in the program (Abrams, Myer, Rosenfield, & El-Sadr, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent evidence suggests that psychosocial factors and depression are interrelated. Studies conducted in sub-Saharan Africa have identified associations between depressive symptoms and both low levels of social support [15] and high levels of HIV-related stigma [16, 17], and recent research conducted among HIV-infected men and women in South Africa has reported that both HIV-related stigma and social support are independently associated with depression [18]. However, the interrelationships among these constructs are poorly understood, and most previous research has not explored the potentially moderating effect of these factors on the relationships between other factors and depression.…”
Section: Introductionmentioning
confidence: 99%
“…Stigma has consistently been associated with a number of mental health difficulties in cross-sectional and prospective analyses, including increased levels of anxiety, depression, and hopelessness, as well as decreases in self-esteem [12][13][14][15][16][17][18]. In addition, PLWH may face social consequences, such as negative social interactions [19] or loss of social support [17].…”
mentioning
confidence: 99%